Indicators of human sociality in Slovenia and the Netherlands - Velkavrh, Žiga (Teorija in praksa, 2022)
In the article we report a series of experiments with volunteers designed to detect differences in behavioural characteristics among Slovenian, Dutch and international students. Using eight standard tasks from experimental economics, we investigate the differences using experimental measures of solidarity, trust, cooperation, positive and negative reciprocity, competition, honesty, and risk attitudes. No significant cohort effects in any of the eight decisions are found when we compare the Slovenian and international cohorts. Still, when comparing the Dutch and Slovenian cohorts, Dutch students are found to exhibit lower levels of solidarity, generosity and honesty. This points to differences in sociality between institutionally similar yet ideologically distant countries like Slovenia and the Netherlands.
Keywords: cross-national study; eksperimentalna ekonomija; experimental economics; game theory; meddržavna študija; sociality; socialnost; Solidarnost; Študenti; teorija iger